Pharmacokinetics and pharmacodynamics of glycopyrrolate following a continuous‐rate infusion in the horse. Issue 2 (31st July 2013) - Rumpler, M. J.; Kandala, B.; Vickroy, T. W.; Hochhaus, G.; Sams, R. A.
<x xml:space="preserve">Abstract</x> Glycopyrrolate (GLY) is an antimuscarinic agent that is used in humans and domestic animals primarily to reduce respiratory tract secretions during anesthesia and to reverse intra‐operative bradycardia. Although GLY is used routinely in veterinary patients, there is limited information regarding its pharmacokinetic (PK) and pharmacodynamic (PD) properties in domestic animals, and an improved understanding of the plasma concentration–effect relationship in racehorses is warranted. To accomplish this, we characterize the pharmacokinetic–pharmacodynamic (PK‐PD) actions of GLY during and after a 2‐h constant‐rate intravenous infusion (4 μg/kg/h) and evaluate potential PK‐PD models for cardiac stimulation in adult horses. Measurements of plasma GLY concentrations, heart and respiration rates, and frequency of bowel movements were performed in six Thoroughbred horses. The time course for GLY disposition in plasma followed a tri‐exponential equation characterized by rapid disappearance of GLY from blood followed by a prolonged terminal phase. Physiological monitoring revealed significant (P < 0.01) increases in heart (>70 bpm) and respiratory rates accompanied by a marked and sustained delay in the frequency of bowel movements (1.1 ± 0.2 h [saline group] vs. 6.0 ± 2.0 h [GLY group]). Two of six horses showed signs of colic during the 8‐h observation period after the end of the GLY infusion, but were treated and recovered without further complications. The relationship between plasma GLY concentration and heart rate exhibited counterclockwise hysteresis that was adequately described using an effect compartment.